Process Intensification Principles Applied to Thermal Energy Storage Systems—A Brief Review - Guo, Xiaofeng; Goumba, Alain Pascal (Frontiers in Energy Research, 2018)
Process intensification (PI) technologies represent all approaches leading to size reduction and efficiency improvement of process equipment. Thermal Energy Storage (TES) systems are key elements in renewable and recovery thermal energy deployments and their performance can benefit from PI principles. This study covers a brief analysis and state of the art of several PI technologies applied to TES systems. All sensible, latent and thermochemical storage systems are covered. Two surface-to-volume ratios closely related to component size and system performance are first analysed. They theoretically show how PI principles may inspire the performance enhancement of TES systems. Then, a brief synthesis on successful PI applications in sensible, latent and thermochemical storages is given. Their approaches mainly consist of thermal stratification preservation, modular design, heat and mass transfer enhancement as well as material properties modification. Finally, potential TES system improvement directions based on PI principles are recommended.